EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN TIPE RECIPROCAL PEER TUTORING (RPT) DITINJAU DARI MOTIVASI BERPRESTASI SISWA KELAS VIII SMP NEGERI DI KABUPATEN SUKOHARJO TAHUN AJARAN 2010/2011 - Nurtesti Nurtesti (Universitas Sebelas Maret, 2012)
Abstract This research aims to determine: (1) which provides a better achievement between cooperative learning of TGT type and cooperative learning of RPT type, (2) which has a better achievement between students who have high achievement motivation, medium and low, (3) which provides a better learning mathematics achievement between learning with TGT type or RPT type on achievement motivation respectively high, medium or low, (4) which provides a better learning mathematics achievement among high, medium or low motivation achievement on learning with TGT type, and (5) which provides a better learning mathematics achievement among high, medium or low motivation achievement on learning with RPT type.The population of this research was the eighth grade students of sukoharjo junior high school, second semester in the Academic Year 2010/2011. The sample size are 220 students taken from the SMP Negeri 1 Kartasura class VIII F and VIII F, SMP Negeri 2 Kartasura class VIII B and VIII C, and SMP Negeri 2 Gatak class VIII F and VIII G. Research sampling technique is stratified cluster random sampling. The instruments used to collect data is studying mathematics achievement tests and questionnaires student achievement motivation. Before the matehamtics achievement test and filling questionnaire of achievement motivation, we first conducted the instrument’s trial. In trials of research mathematics achievement test, it was conducted a test on the level of difficulty items, the distinguishing and reliability. The achievement motivation questionnaire was conducted on internal consistency and reliability. The research of the preliminary test proved that those samples are normally distributed with the homogeneous variance and balanced. Than we conducted test of hypothesis using two-way analysis of variance (ANOVA) model with unequal cell frequencies to 5% significance level. Prior to that, pre-requisite test: normality using the Lilliefors test and homogeneity of variances using the Bartlett test. The results of pre-requisite test are samples come from population with normal distribution and have homogeneity of variancesFrom the analysis, it was concluded that: (1) cooperative learning of TGT type give the same learning mathematics achievement with cooperative learning of RPT type, (2) students with high achievement motivation have to learn mathematics achievement better than students with medium and low achievement motivation, and students with medium and low achievement motivation has the same learning mathematics achievement, (3) learning model with the type of TGT and type of RPT result do not differ when given to students with high achievement motivation and students with low achievement motivation, but learning to type of TGT provide learning mathematics achievement is better than learning by students with the type of RPT on students with medium achievement motivation, (4) with the type of TGT, students with high, medium and low achievement motivation has the same learning mathematics achievement, (5) with the type of RPT, learning mathematics achievement students with high achievement motivation better than students with medium achievement motivation, while students with medium and low achievement motivation has the same learning mathematics achievement. Keywords: Teams Games Tournament, Reciprocal Peer Tutoring, Achievement Motivation, Learning Mathematics Achievement